THE EFFECT OF GUIDED INQUIRY LEARNING MODEL ON STUDENT’S LEARNING OUTCOMES IN TOPIC DYNAMIC ELECTRICITY IN CLASS X SEMESTER II SMA N 2 KISARAN A.Y.2014/2015 - Lia Anggraini Siregar; Motlan . (INPAFI (Inovasi Pembelajaran Fisika), 2015)
ABSTRACT The research aimed to know the influence ofguided inquiry learning model on student’s learning outcomes in topic dynamic electricity in class X semester II SMA N 2 Kisaran A.Y 2014/2015. Beside that, the research also aimed to determine the differences between students learning outcomes by using guided inquiry learning model and conventional learning, and to know the student’s activities as affective and psychomotor. The research used a quasi-experimental method. The population were all students of class X consist of 8 classes. The samples defined by cluster random sampling and conducted in class X-1 as the experiment class and X-2 as the control class. The instruments were used learning outcomes test and the observation sheet.The result showed that the average value of posttest in experiment class is 64.25 higher than in control class is 53. The hypothesis result of posttest in experiment class and control class get >, so Ha can be accepted. The observation result showed student’s activity in experiment class included in active category. Finally, it can be concluded that there is an effect of guided inquiry learning model on student’s learning outcomes in topic dynamic electricity.   Keywords : guided inquiry learning model, student’s learning outcomes, affective, psychomotor